Analisis Faktor-faktor yang Mempengaruhi Pemilihan Merek Telepon Seluler di Kota Lhokseumawe - Matriadi, Faisal (Jurnal Aplikasi Manajemen, 2008)
Research aim to to know factors what influencing election of brand phone seluler in town of Lhokseumawe. used Data in the form of data of sekunder, obtained through spreading of quesioner to 75 responder people using six-month minimum ponsel. In analysing this research used by analyzer, that is for the analysis of diskriptif, appliance the used is frequency. percentage, and mean that is scale of lingkert and of regresi doubled linear of Y = bo + b1x1 + b2x2 + b3x3 + e. Result of research met by influence of social factor (X), personal factor (X), and psychological factor (X) conducted with testing value of r2. pursuant to result of examination, hence found by value of r equal to 0.930 meaning that influence of observation variable to variable dependen if conducted to the each variable equal to 0.930 (93%) the rest equal to 0.7 (7%) influenced by other factor. Meanwhile assess requal to 0.866 meaning that if observation variables tested simultaneously only can influence consumer choice equal to 0,866 (86,6%) while the rest equal to 0,134 (13,4%) other influenced by other factors which do not be packed into research model. Result of examination found that value of F-Test equal to 152.383 much more is big compared to critical value of F-Tabel which only equal to 4,826 thereby this examination have up to standard to accept alternative hypothesis (Hi) and refuse hypothesis zero (Ho).